Textured mat influence on muscle activity and balance strategies for chronic ankle instability - Konphet, Nanthiphak; Siriphorn, Akkradate (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. To evaluate the impact of textured mats on muscle activation and postural sway to enhance neuromuscular control and balance strategies in the rehabilitation of chronic ankle instability (CAI).Methods. Using a within-subject design, we measured centre of mass (CoM) acceleration and muscle activation in 28 CAI patients on firm, foam, and textured surfaces during double-leg and single-leg stances. Electromyography (EMG) measured muscle activity, while an integrated accelerometer in the EMG unit captured CoM acceleration. Statistical analysis using the Friedman test for overall differences across conditions and Dunn’s test for pairwise comparisons, with significance set at p < 0.05.Results. CoM acceleration decreased on the textured mat during single-leg stances compared to the foam surface, indicating a moderated balance challenge. The textured mat also significantly reduced muscle activity compared to the foam surface across all conditions. However, it enhanced the activation of key muscles – vastus medialis and medial gastrocnemius – during double-leg stances compared to the firm surface.Conclusions. The textured mat provided a unique stimulus that facilitated specific muscle engagement and improved proprioception without destabilizing balance. This suggests a potential value in early CAI rehabilitation phases.
Keywords: ankle injuries; postural balance; electromyography; muscle contraction